Механическое зарядное устройство 1.0; Архитекторы будущего - Адамов Е. В. Егор Владимирович; Серебренников М. А. Максим Анатольевич; Серенко А. Анастасия; Бабинская Я. Ярославна (2014, 2014)
Заглавие с титульного экрана